Determinantes para la internacionalización de las pymes en la ciudad de Riobamba-Ecuador, período 2020 - Edgar Alexander, Allauca Ortega (2021)
ABSTRACT The objective of the globalization process is to study the determinants that allow the internationalization of small and medium-sized enterprises (SMEs), in the Riobamba city - Ecuador during the 2020 period, using the hypothetical deductive method and based on the documentary and field approaches managers of 102 SMEs surveyed. The econometric model used was logit that relates the factors raised in this research: international alliances, financing, support networks, technological level, psychic distances, company size, experience, technological capacity, quality certifications. The results show that the experience and the reduction of psychic distances are variable in favor of the internationalization of SMEs in order to export their products internationally. Keywords: SMEs, Internationalization, Determining factors, Economic development, Export. Reviewed by: Mgs. Maritza Chávez Aguagallo ENGLISH PROFESSOR c.c. 0602232324